2019
DOI: 10.1016/s2352-3026(19)30021-3
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral haemopoietic stem/progenitor cell gene therapy for treatment of Wiskott-Aldrich syndrome: interim results of a non-randomised, open-label, phase 1/2 clinical study

Abstract: Background Wiskott-Aldrich syndrome is a rare, life-threatening, X-linked primary immunodeficiency characterised by microthrombocytopenia, infections, eczema, autoimmunity, and malignant disease. Lentiviral vector-mediated haemopoietic stem/progenitor cell (HSPC) gene therapy is a potentially curative treatment that represents an alternative to allogeneic HSPC transplantation. Here, we report safety and efficacy data from an interim analysis of patients with severe Wiskott-Aldrich syndrome who received lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 33 publications
(72 reference statements)
5
152
0
1
Order By: Relevance
“…IS analysis in T cells with a vector copy number ranging from 1 to 3 per cell revealed that the frequency at which ISs were found in proto-oncogenes (and notably in LMO2 ) was much reduced (Hacein-Bey-Abina et al, 2014). Interestingly, no cases of leukemia have occurred in clinical trials based on the use of SIN vectors (whether γRV or LV constructs to transduce ex vivo CD34 hematopoietic progenitors in different diseases), since the 44 patients with ≥4 yr of follow-up are all leukemia free (Cartier et al, 2009; Cavazzana-Calvo et al, 2010; Aiuti et al, 2013; Biffi et al, 2013; Hacein-Bey-Abina et al, 2014; Ferrua et al, 2019; Sessa et al, 2016; Hacein-Bey Abina et al, 2015). T cell reconstitution was achieved in all but two patients treated with the SIN γRV-IL2RG vector associated with a major clinical benefit.…”
Section: Adverse Events and Clinical Trials Based On Second-generation Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…IS analysis in T cells with a vector copy number ranging from 1 to 3 per cell revealed that the frequency at which ISs were found in proto-oncogenes (and notably in LMO2 ) was much reduced (Hacein-Bey-Abina et al, 2014). Interestingly, no cases of leukemia have occurred in clinical trials based on the use of SIN vectors (whether γRV or LV constructs to transduce ex vivo CD34 hematopoietic progenitors in different diseases), since the 44 patients with ≥4 yr of follow-up are all leukemia free (Cartier et al, 2009; Cavazzana-Calvo et al, 2010; Aiuti et al, 2013; Biffi et al, 2013; Hacein-Bey-Abina et al, 2014; Ferrua et al, 2019; Sessa et al, 2016; Hacein-Bey Abina et al, 2015). T cell reconstitution was achieved in all but two patients treated with the SIN γRV-IL2RG vector associated with a major clinical benefit.…”
Section: Adverse Events and Clinical Trials Based On Second-generation Vectorsmentioning
confidence: 99%
“…The treatment appears to have effectively induced the differentiation of WASp-expressing leukocytes and platelets. This expression has translated into the high-quality reconstitution of immune functions, including T and B cell functions, and the control of infections, allergy, and autoimmunity (Aiuti et al, 2013; Hacein-Bey Abina et al, 2015; Ferrua et al, 2019). The level of WASp expression, however, did not usually reach that of wild-type cells.…”
Section: Extension Of Indicationsmentioning
confidence: 99%
“…Nowadays, hematopoietic stem cell transplantation (HSCT) remains the main curative treatment of many hematological malignancies and for inherited genetic disorders, 1,2 together with HSPC-based GT. 3,4,[36][37][38][39][40][41] In this context, understanding the role of HSPC subpopulations after transplantation is of paramount importance for the improvement of clinical procedures aimed at establishing not only LT maintenance of the graft but also early recovery from cell aplasia.…”
Section: Role Of Human Hspc After Transplantationmentioning
confidence: 99%
“…Once diagnosed and treated appropriately, patients can often lead relatively normal lives (4,5). Curative therapies are also possible, depending on the disorder, with hematopoietic stem cell transplantation (HSCT), enzyme replacement therapy (ERT), or gene therapy (5)(6)(7)(8)(9)(10)(11). Almost ubiquitously, early detection of PIDDs is extremely important in controlling and preventing potentially life-threatening infections and chronic sequelae (12,13).…”
Section: Introductionmentioning
confidence: 99%